Perkembangan Industri Furnitur Kabupaten Jepara Serta Kaitannya Dengan Potensi Penerimaan Pajak - Shandy Jannifer Matitaputty; Westri Kekalih; Agnes Arie M. Christie; Paulina Rini Hastuti (Soegijapranata Catholic University, 2020)
Jepara Regency is one of the areas that is the center of the furniture industry in Indonesia. The development of the furniture industry is expected to increase regional income and tax revenue. This study discusses to look at the development of the furniture industry in Jepara Regency, asking for the development of the furniture industry with Jepara Regency revenue as well as potential tax revenues related to the development of the Jepara Regency furniture industry. This research uses quantitative descriptive analysis method. The quantitative descriptive analysis used includes trend analysis, analysis of the furniture industry tax, and Input-Output (I-O) analysis. The results showed; 1. Furniture Industry in Jepara Regency still has an upward trend of development from year to year both in terms of the number of business units, production volume and number of workers, 2. The Furniture Industry has an important role in developing Jepara Regency in terms of labor, 3 The role / relationship of the furniture / wood material industry in Jepara Regency to other sectors to input suppliers or related future links above the regional average. 4. Increase in taxes in accordance with government taxes, but the potential for tax revenue from the furniture business industry in Jepara Regency shows a positive trend.